2019
DOI: 10.1002/pa.2043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foreign direct investment, remittances, and foreign aid on economic growth: Evidence from two emerging South Asian economies

Abstract: This paper analyzes the effect of foreign direct investment, remittances, and official development assistance on economic growth in India and Sri Lanka. The study uses annual time series data of both countries for the period 1980–2016. In order to find the short‐run and long‐run relationship among the variables, we use Granger causality test and vector error correction model. We also carry out a vector decomposition analysis to predict the forecast variance error of the future periods and impulse response func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…In summary of empirical review, this study differs from earlier empirical studies, which either examined the relationship between foreign aid and economic growth (Asiedu, 2014;Das and Sethi, 2019;Jena and Sethi, 2019;Sethi et al, 2019) or foreign aid and foreign direct investment (Bhavan et al, 2011;Quazi et al, 2014), which neglected the interactive roles of Human capital in foreign aid -economic nexus as emphasised by the Neoclassical growth theory that provided the underpinning for the study. IJDI 20,2…”
Section: Empirical Literaturementioning
confidence: 95%
“…In summary of empirical review, this study differs from earlier empirical studies, which either examined the relationship between foreign aid and economic growth (Asiedu, 2014;Das and Sethi, 2019;Jena and Sethi, 2019;Sethi et al, 2019) or foreign aid and foreign direct investment (Bhavan et al, 2011;Quazi et al, 2014), which neglected the interactive roles of Human capital in foreign aid -economic nexus as emphasised by the Neoclassical growth theory that provided the underpinning for the study. IJDI 20,2…”
Section: Empirical Literaturementioning
confidence: 95%
“…Their findings from empirical estimations suggest that while foreign aid is negatively associated with FDI as well as growth, FDI positively influences growth. Das and Sethi (2019) analyzed the effect of FDI, remittances and official development assistance on economic growth in India and Sri Lanka. They found that that FDI and remittances have a significant impact on economic growth in India, whereas in Sri Lanka, foreign aid and remittances play an important role in enhancing economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Adenutsi 2010 They found that inward remittance is affecting export performance negatively during the study period. Das and Sethi (2019) Table 4.…”
Section: Empirical Literaturementioning
confidence: 99%
“…They found that inward remittance is affecting export performance negatively during the study period. Das and Sethi (2019) analyzed the effect of foreign direct investment, remittances, and official development assistance on economic growth in India and Sri Lanka. They found that that foreign direct investment and remittances have a significant impact on economic growth in India, whereas in Sri Lanka, foreign aid and remittances play an important role in enhancing economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%